Project Based Dıgıtal Vıdeo Approach to Improve Student Competencıes - Lim Seh Hoe, Tay Choo Chuan (International Journal of Advanced Science and Technology, 2020)
The aim of this research study is to provide a framework as a set of guideline for the change of pedagogical teaching method in secondary school. Thus, project-based learning (PBL) is a key to support students to be more competitive in an external environment. The respondents were given 4 weeks to plan and organized the video project. Likert-type questionnaire is developed to identify students’ viewpoint on the PBL method in enhancing student competencies. The data was collected through questionnaire from 63 respondents. There is a positive significant result in terms of student competencies through PBL framework which provides appropriate structure in determining the level of student competencies. Students able to produce an educational based video on the topic they are learning. By integrating technology in Malaysia Education Curriculum through PBL, student competencies, which consist of communication, collaboration, creation and critical thinking was enhanced. PBL framework provides appropriate structure for determining the level of student competencies. This paper gives a framework which serves as a reference to facilitate the relevant policy- making in the secondary school education trend. This study contributes to the understanding on how PBL should be implemented in the classrooms to encourage students in to pursuing STEAM majors at the higher level.